CRISIS OF MUSLIM CIVILIZATION IN MODERN TIMES - Dr. Faraz Anjum (Journal of Islamic Thought and Civilization, 2011)
No one would, probably, doubt that Muslim civilization is facing a serious crisis since the 18th century. It first resulted in political chaos and ultimately colonization of Muslim lands by Western powers. Later, Muslim civilization faced serious cultural and intellectual onslaught from the West which intensified and deepened the crisis. Though the period of Western colonization ostensibly came to an end in the middle of the 20th century, Muslim lands did not come out of the crisis. Despite some sincere efforts for Islamic revivalism, Muslim civilization has failed to respond to the modern crisis, particularly 9/11 incident has exposed the vulnerability of the Muslim world to Western political agenda, and its failure to respond effectively to Western civilizational challenges. The scholars are divided as to the cause of this crisis of the Muslim world and consequently, as to the measures to remedy the problem. Abdur Rehman Ibn Khaldun, a 13th century Muslim historian and intellectual, emerged at a time when the Muslim states in the Maghreb (North Africa) and Muslim Spain were passing through a phase of decline. His critical thoughts on the society (Al-Imran) and particularly his concept of social solidarity (Al-asabiyah), as propounded in his magnum opus, Maqaddimah (Prolegomena to History), can provide important insights into the present crisis of the Muslim Civilization. The present paper seeks to understand and explain this crisis with the help of the social analysis and critical ideas of Ibn Khaldun.